Translating non-binary coming-out reports: Gender-fair language strategies and use in news articles - Lardelli, Manuel; Gromann, Dagmar (The Journal of Specialised Translation, 2023)
With the increased visibility of non-binary people, more and more strategies have been proposed for gender-fair language in languages that have grammatical gender, such as German. Gender-fair is used as an umbrella term for gender-inclusive, the explicit inclusion of all genders beyond the binary, and gender-neutral strategies, which omit any gender-specific references in language. An in-depth overview of these strategies has not yet been provided and very few studies analyse their use. This article proposes an in-depth introduction to gender-fair language strategies in German and Italian and their use in news articles. To this end, we compiled a corpus of news articles on the coming out of Demi Lovato as non-binary in both languages, which were all based on and translated from Lovato’s original Twitter post in English. To investigate translation strategies for gender-fair language, we analyse which gender-fair language strategy was applied to translate the tweet. Furthermore, the use and frequency of gender-fair pronouns, nouns, and adjectives were investigated in each article. Results show that misgendering is still very common, especially in Italian. A dominant strategy was not found in German or in Italian; a mix of gender-neutral and gender-inclusive forms was used instead.